Direct numerical simulation of infusion and flow-front tracking in materials with heterogeneous permeability using a pressure mapping sensor. (June 2020) - Levy, Arthur; Kratz, James
This paper explores the use of thin film piezoresistive pressure mapping sensors as a means to improve resin transfer moulding processes. The pressure mapping sensor was located between the preform and mould, giving information regarding the permeability map prior to infusion. The permeability map is used as an input to a direct numerical simulation of the infusion step of a highly variable reclaimed carbon fibre preform. The pressure sensor was also used to track the flow front position in-situ, due to a change in load sharing between the preform and liquid during the infusion experiment. Flow front tracking with the pressure mapping sensor was validated against conventional camera images taken through a transparent mould. The direct numerical simulation was able to account for local permeability variation in the preform, providing improved flow-front prediction than homogeneous permeability only, and could be part of a wider strategy to improve resin transfer moulding process robustness.